Increasing Perceptual Salience Diminishes the Motor Interference Effect From Dangerous Objects - Cao, Rong; Cao, Gai; Liu, Peng (Frontiers in Psychology, 2020)
Existing research has indicated that dangerous objects may conflict with an individual’s prepared motor actions and thus slow responses. This phenomenon is called the motor interference effect from dangerous objects. However, its origin remains arguable. The current study aimed to preclude an alternative origin and to investigate whether the efficiency of processing a prepared response towards a dangerous object could benefit from increasing the perceptual salience of the object by painting the object red. The design used a shape categorization task to emphasize the dangerous elements of target objects and manipulated target color (gray versus red), target dangerousness (safe versus dangerous) and prime-target congruency (congruent versus incongruent). The null effect of N2 amplitudes between the dangerous and safe conditions precluded the alternative origin and suggested that the motor interference effect did not originate from response inhibition. Furthermore, the results indicated a modulation effect of the motor interference effect in different colors. The classic motor interference effect was observed in the gray target condition, but it diminished in the red target condition. The underlying cognitive processes were reflected in ERPs. More positive P2 and frontal P3 amplitudes were identified in the red target condition than in the gray target condition, which indicated that deeper feature detection was assigned to and more attentional resources were automatically recruited for the red targets than for the gray targets. Analysis of the parietal P3 amplitudes identified a similar result pattern as the mean RTs. A more positive P3 amplitude was identified in the dangerous condition than in the safe condition when the targets were painted gray. In contrast, the P3 amplitudes were identical between the dangerous condition and the safe condition when the targets were painted red. The results indicated that the increased attentional resources facilitated the evaluation of red target dangerousness and thus accelerated reactions to the red dangerous targets; the reaction speeds to those targets were close to those for the reaction speeds to the red safe targets. Detailed processes that underline these components are discussed.